2015
DOI: 10.1128/aac.01048-15
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Ex Vivo Efficacies of “Reversed Chloroquine” Compounds in Chloroquine-Resistant Plasmodium falciparum and P. vivax Isolates

Abstract: h Chloroquine (CQ) has been the mainstay of malaria treatment for more than 60 years. However, the emergence and spread of CQ resistance now restrict its use to only a few areas where malaria is endemic. The aim of the present study was to investigate whether a novel combination of a CQ-like moiety and an imipramine-like pharmacophore can reverse CQ resistance ex vivo. Between March to October 2011 and January to September 2013, two "reversed chloroquine" (RCQ) compounds (PL69 and PL106) were tested against mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…2 . These ex vivo drug susceptibility data are in concordance with ex vivo IC 50 estimates produced in parallel studies in the area confirming a high level of CQ resistance in both Plasmodium species in Papua Indonesia [ 37 , 38 ].
Fig.
…”
Section: Resultssupporting
confidence: 79%
“…2 . These ex vivo drug susceptibility data are in concordance with ex vivo IC 50 estimates produced in parallel studies in the area confirming a high level of CQ resistance in both Plasmodium species in Papua Indonesia [ 37 , 38 ].
Fig.
…”
Section: Resultssupporting
confidence: 79%
“…Comparing findings of the present study to those reported previously for P. falciparum and P. vivax isolates from the Brazilian Amazon [ 46 , 47 ] and Indonesia [ 36 , 48 , 49 ] using pLDH ELISA and SMT assays, Cambodian isolates were found to be less susceptible to MQ and PPQ. However, Cambodian and Brazillian P. vivax isolates were more sensitive to CQ than in Papua Indonesia where P. vivax CQ resistance has emerged.…”
Section: Discussionsupporting
confidence: 77%
“…falciparum and P. vivax isolates collected from the same area where the isolates for the current study were collected, and the two species showed different profiles of susceptibility to the two compounds (39). Whereas the IC 50 s of both compounds were significantly lower than the IC 50 of CQ alone in P.…”
Section: Discussionmentioning
confidence: 97%